Radiação cósmica de fundo: anisotropias, polarização e parâmetros cosmológicos - Guaitolini Junior, Judismar Tadeu (2012)
The cosmic microwave background radiation is the oldest sign that we detect in the universe today, and it consists of an electromagnetic radiation with maximum intensity in the microwave range, with temperature of 2.725 K, and which dates from a period when the first hydrogen atoms could form in a dense and hot universe. Together with the measures of the recession of galaxies and the abundance of light elements, the cosmic microwave background radiation and the information derived from it, form the pillars of modern cosmology, in agreement with the Big Bang model. In this work we review the anisotropies in temperature and polarization of the cosmic microwave background radiation, with emphasis on the cosmological parameters associated with these phenomena, we obtain the angular power spectrum associated with the temperature of this radiation in a detailed manner, and we seek to gradually build the ideas, with the purpose of making this work as accessible as possible for those who do a first reading of the subject